Strawberry Polyphenol-Rich Fractions Can Mitigate Disorders in Gastrointestinal Tract and Liver Functions Caused by a High-Fructose Diet in Experimental Rats - Ewa Żary-Sikorska; Bartosz Fotschki; Monika Kosmala; Joanna Milala; Paulius Matusevicius; Aleksandra Rawicka; Jerzy Juśkiewicz (Polish Journal of Food and Nutrition Sciences)
In the current study, it was hypothesized that the addition of strawberry polyphenol-rich fractions to a high-fructose diet mitigates disorders in liver functions, lipid metabolism, and in the antioxidant and pro-inflammatory status of rats. Therefore, a fraction rich in ellagitannins and proanthocyanidins (EP), and a fraction containing compounds of both mentioned classes of polyphenols and additionally anthocyanins (EPA), in doses of 0.28 and 0.70 g/100 g, respectively, were added to a standard or a high-fructose diet administered to rats for six weeks. The EPA fraction was more beneficial in alleviating the consequences of consuming excess fructose in the diet than the EP fraction. Probably, that fraction containing considerable amounts of carbohydrates was more extensively metabolized by intestinal bacteria, which resulted in higher levels of cecal short chain fatty acids (SCFAs) as well as cecal and urinal ellagitannin metabolites. As a further consequence, diet supplementation with the EPA fraction caused more favorable changes in the levels of serum interleukin 6 and serum antioxidant capacity of water-soluble substances (ACW), in atherogenicity index lg((triglyceride/high-density lipoprotein cholesterol), hepatic oxidized glutathione as well as reduced to oxidized glutathione ratio). Efforts should be made to develop strawberry polyphenol-rich preparations containing the preferred anthocyanins, which is, however, difficult due to the instability of this class of phenolic compounds during the technological process.